2022
DOI: 10.3390/ijerph192316346
|View full text |Cite
|
Sign up to set email alerts
|

The Associations between Sibling Victimization, Sibling Bullying, Parental Acceptance–Rejection, and School Bullying

Abstract: Bullying has been identified as the most common form of aggression experienced by school-age youth. However, it is still unclear about the family’s influence on school bullying. Therefore, the current study aimed to explore the associations between sibling bullying and school bullying, sibling victimization and school victimization, and parental acceptance–rejection and school bullying victimization. The study was cross-sectional and conducted on a sample of students aged between 11 and 20 years recruited from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 69 publications
0
8
0
Order By: Relevance
“…The following fit indices were used to examine data-model fit: the p-value of the chi-squared statistic (non-significant), comparative fit index (CFI) (≥0.90), standardized root-mean-squared residual (SRMR) (≤0.08), and root-mean-squared error of approximation (RMSEA) (≤0.08) [33,39,[56][57][58][59]. By examining the relationship between the observed data and the expected factor structure, the CFA provided insights into how well the items were related to the measured latent construct [31,56,[60][61][62]. In addition, Cronbach's alpha, Composite Reliability, and MaxR(H) were used to estimate the scale's internal reliability.…”
Section: Discussionmentioning
confidence: 99%
“…The following fit indices were used to examine data-model fit: the p-value of the chi-squared statistic (non-significant), comparative fit index (CFI) (≥0.90), standardized root-mean-squared residual (SRMR) (≤0.08), and root-mean-squared error of approximation (RMSEA) (≤0.08) [33,39,[56][57][58][59]. By examining the relationship between the observed data and the expected factor structure, the CFA provided insights into how well the items were related to the measured latent construct [31,56,[60][61][62]. In addition, Cronbach's alpha, Composite Reliability, and MaxR(H) were used to estimate the scale's internal reliability.…”
Section: Discussionmentioning
confidence: 99%
“…Parke et al (2001) [39] argue that conflict resolution tactics develop in the personal interrelationship between siblings and are later transferred to negotiation within one's group of peer friends. The literature supports these conclusions, associating the conflicts that arise in the sibling context with those that occur in the peer context (e.g., [17,[40][41][42][43][44]).…”
Section: Introductionmentioning
confidence: 86%
“…Fourthly, the study did not consider bullying inside households. Sabah et al observed that the effect of sibling physical and sibling verbal victims on school victimization was statistically significant [53]. Future studies could therefore consider bullying within the family to explore the extent to which the increase in the prevalence of all types of school bullying during the pandemic was related to school bullying and the extent to which it was related to bullying inside households.…”
Section: Limitationsmentioning
confidence: 99%